Positive : surviving my bullies, finding hope, and living to change the world --a memoir - Rawl, Paige (Harper, an imprint of HarperCollinsPublishers, 2014)
"A teenager's memoir of the experinces of bullying, being HIV positive and surviving the experiences to become a force for positive change in this world"--